Inhibition of cellulase activity by liquid hydrolysates from hydrothermally pretreated soybean straw - Kim, Daehwan; Ji, Anqi; Jackson, Armoni L.; Brown, Bailee; Kim, Youngmi; Kim, Sun Min; Laufer, Craig; Ferrier, Drew; Yoo, Chang Geun (Frontiers in Chemical Engineering, 2022)
The one-pot biomass conversion process is a promising strategy to minimize the potential product loss and reduce processing costs. However, this strategy has technical limitations due to the inhibitory effects of biomass components like lignin as well as the generated inhibitors (e.g., furans, phenols) during biomass processing. In this study, the inhibitory effects of liquid hydrolysates formed by hydrothermal pretreatment of soybean straw with either sodium hydroxide or hydrogen peroxide on cellulolytic enzyme activity were investigated. Hydrothermal pretreatment of soybean straw (10% w/v) was carried out with either sodium hydroxide (1% v/v) or hydrogen peroxide (1% v/v) at 121 oC for 60 min to evaluate the effect of water-soluble inhibitors released from soybean pretreatment on cellulolytic enzyme activity. The fraction of cellulose in pretreated solids (1% w/v glucan) was enzymatically hydrolyzed for 72 h with 25 mg enzyme protein/g glucan in the presence of either buffer or liquid hydrolysate generated from the pretreatments. Hydrolysis of NaOH and H2O2 pretreated solids resulted in 57% and 39% of glucose yields in buffer, respectively. In the presence of the liquid hydrolysates, NaOH and H2O2 pretreated biomass showed 20% and 30% glucose yield, respectively, indicating the enzyme suppression by inhibitors in the liquid hydrolysates. Of the enzyme activities in hydrolysates tested, NaOH hydrolysate showed a higher inhibitory effect on enzyme activities (mainly β-glucosidase) compared to H2O2 liquid, where enzyme deactivation has a first-order correlation and the manner in which the vacuum-filtered inhibitors were generated from pretreated soybean straw.